Accurate Molecular Orientation Analysis Using Infrared p-Polarized Multiple-Angle Incidence Resolution Spectrometry (pMAIRS) Considering the Refractive Index of the Thin Film Sample. Issue 6 (June 2017) - Shioya, Nobutaka; Shimoaka, Takafumi; Murdey, Richard; Hasegawa, Takeshi
Infrared (IR) p-polarized multiple-angle incidence resolution spectrometry (pMAIRS) is a powerful tool for analyzing the molecular orientation in an organic thin film. In particular, pMAIRS works powerfully for a thin film with a highly rough surface irrespective of degree of the crystallinity. Recently, the optimal experimental condition has comprehensively been revealed, with which the accuracy of the analytical results has largely been improved. Regardless, some unresolved matters still remain. A structurally isotropic sample, for example, yields different peak intensities in the in-plane and out-of-plane spectra. In the present study, this effect is shown to be due to the refractive index of the sample film and a correction factor has been developed using rigorous theoretical methods. As a result, with the use of the correction factor, organic materials having atypical refractive indices such as perfluoroalkyl compounds ( n = 1.35) and fullerene ( n = 1.83) can be analyzed with high accuracy comparable to a compound having a normal refractive index of approximately 1.55. With this improved technique, we are also ready for discriminating an isotropic structure from an oriented sample having the magic angle of 54.7°.